Immunotherapy for ocular melanoma: a bibliometric and visualization analysis from 1991 to 2022 - Tan, Yao; Lu, Yijie; Chen, Sheng; Zou, Chang; Qin, Bo (Frontiers in Oncology, 2023)
Background: In recent years, new therapeutic options to overcome the mechanisms of tumor immune suppression be effective in the treatment of cutaneous melanoma. These approaches have also been applied in ocular melanoma. The aim of this study is to present the current status and research hotspots of immunotherapy for ocular melanoma from a bibliometric perspective and to explore the field of immunotherapy for malignant ocular melanoma research. Results: A total of 401 papers and 144 reviews related to immunotherapy of ocular melanoma were included. The United States is the main driver of research in the field, ranking first in terms of the number of publications, total citations, and H-index. The UNIVERSITY OF TEXAS SYSTEM is the most active institution, contributing the most papers. Jager, Martine is the most prolific author, and Carvajal, Richard is the most frequently cited author. CANCERS is the most published journal in the field and J CLIN ONCOL is the most cited journal. In addition to ocular melanoma and immunotherapy, the most popular keywords were "uveal melanoma" and "targeted therapy". According to keyword co-occurrence and burst analysis, uveal melanoma, immunotherapy, melanoma, metastases, bap1, tebentafusp, bioinformatics, conjunctival melanoma, immune checkpoint inhibitors, ipilimumab, pembrolizumab, and other research topics appear to be at the forefront of this field's research and have the potential to remain a hot research topic in the future. Conclusion: This is the first bibliometric study in the last 30 years to comprehensively map the knowledge structure and trends in the field of research related to ocular melanoma and immunotherapy. The results comprehensively summarize and identify research frontiers for scholars studying immunotherapy associated with ocular melanoma.